Citrulline levels in preterm infants: A clinical comparison between suspected necrotizing enterocolitis and healthy controls - Atmaja, Birgitta Suparman Supa; Athiyyah, Alpha Fardah; Etika, Risa; Darma, Andy; Sumitro, Khadijah Rizky; Sudarmo, Subijanto Marto (Acta Biomedica Atenei Parmensis, 2026)
Background: Necrotizing enterocolitis (NEC) is a severe acute ischemic condition of the intestine in neonates, with higher incidence and mortality rates among preterm and low birth weight infants. Reliable biomarkers that reflect intestinal functional integrity are crucial for guiding management and monitoring recovery, yet none are routinely available. Plasma citrulline, synthesized by small intestinal enterocytes, reflects enterocyte mass and absorptive function and may serve as a non-invasive indicator of gut maturity and mucosal injury. Methods: A case-control study included 38 preterm infants admitted to NICU and Neo-Intermediate units. Citrulline levels were measured on days 1 and 7 and compared between NEC and healthy groups. Correlations with clinical variables were also analyzed. Results: The NEC group was predominantly male (76.5%; p=0.037) and had significantly higher antibiotic use and CRP levels than the healthy group (p=0.000 and p=0.001). Citrulline levels on day 1 and day 7 did not differ significantly between groups. However, the change in citrulline levels from day 1 to day 7 was significantly different (p=0.001). No significant associations were found with gestational age, birth weight, or NEC severity. A weak but significant correlation was observed between citrulline level on day 1 and birth length (r=0.324, p=0.047). Conclusion: Differences in citrulline change between NEC and healthy infants suggest potential as a predictive biomarker. Although only weakly correlated with birth length, citrulline may provide insight into NEC risk in shorter preterm infants. Further studies are needed to validate these findings.